Enhancing Science Learning Learning Outcomes Through Animated Video Media: Evidence from Indonesian Elementary Education - Maulida Safitri; Moh Irawan Zain; Mansur Hakim (Papanda Publisher, 2026)
Elementary science education faces challenges in visualizing abstract concepts such as the water cycle. This study aimed to examine the effect of animated video learning media on fifth-grade students' IPAS learning outcomes. A quasi-experimental design with nonequivalent control group pretest-posttest was employed with 40 students at SD Negeri 15 Mataram, divided into an experimental group (n=22) using animated videos and a control group (n=18) using conventional methods. Data were collected through multiple-choice tests and analyzed using independent samples t-test. The experimental group achieved significantly higher posttest mean scores of 82.27 (SD=8.91) compared to the control group's 68.89 (SD=9.76), with t(38)=4.482, p<0.001, and mean difference of 13.38 points. Findings support the Cognitive Theory of Multimedia Learning, demonstrating that dual-channel presentation (visual and auditory) optimizes cognitive processing and knowledge construction. Animated videos facilitated visualization of dynamic water cycle processes difficult to observe directly, reduced cognitive load, and supported meaningful learning aligned with constructivist principles. Animated video media significantly enhanced IPAS learning outcomes on water cycle content, providing practical implications for technology integration in science education under the Kurikulum Merdeka framework.